Smyd1b_tv1, a key regulator of sarcomere assembly, is localized on the M-line of skeletal muscle fibers. - Huiqing Li; Jin Xu; Yue-Hong Bian; Pep Rotllant; Tiansheng Shen; Wuying Chu; Jianshe Zhang; Martin Schneider; Shao Jun Du (PLoS ONE)
Background Smyd1b is a member of the Smyd family that plays a key role in sarcomere assembly during myofibrillogenesis. Smyd1b encodes two alternatively spliced isoforms, smyd1b_tv1 and smyd1b_tv2, that are expressed in skeletal and cardiac muscles and play a vital role in myofibrillogenesis in skeletal muscles of zebrafish embryos. Methodology/principal findings To better understand Smyd1b function in myofibrillogenesis, we analyzed the subcellular localization of Smyd1b_tv1 and Smyd1b_tv2 in transgenic zebrafish expressing a myc-tagged Smyd1b_tv1 or Smyd1b_tv2. The results showed a dynamic change of their subcellular localization during muscle cell differentiation. Smyd1b_tv1 and Smyd1b_tv2 were primarily localized in the cytosol of myoblasts and myotubes at early stage zebrafish embryos. However, in mature myofibers, Smyd1b_tv1, and to a small degree of Smyd1b_tv2, exhibited a sarcomeric localization. Double staining with sarcomeric markers revealed that Smyd1b_tv1was localized on the M-lines. The sarcomeric localization was confirmed in zebrafish embryos expressing the Smyd1b_tv1-GFP or Smyd1b_tv2-GFP fusion proteins. Compared with Smyd1b_tv1, Smyd1b_tv2, however, showed a weak sarcomeric localization. Smyd1b_tv1 differs from Smyd1b_tv2 by a 13 amino acid insertion encoded by exon 5, suggesting that some residues within the 13 aa insertion may be critical for the strong sarcomeric localization of Smyd1b_tv1. Sequence comparison with Smyd1b_tv1 orthologs from other vertebrates revealed several highly conserved residues (Phe223, His224 and Gln226) and two potential phosphorylation sites (Thr221 and Ser225) within the 13 aa insertion. To determine whether these residues are involved in the increased sarcomeric localization of Smyd1b_tv1, we mutated these residues into alanine. Substitution of Phe223 or Ser225 with alanine significantly reduced the sarcomeric localization of Smyd1b_tv1. In contrast, other substitutions had no effect. Moreover, replacing Ser225 with threonine (S225T) retained the strong sarcomeric localization of Smyd1b_tv1. Conclusion/significance Together, these data indicate that Phe223 and Ser225 are required for the M-line localization of Smyd1b_tv1.